Kajian Geoteknik untuk Penentuan Geometri Lereng Front Penambangan di PT. XYZ - Muhammad Ikram; Yuliadi (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Geotechnical studies are an important function in overcoming the problem of slope stability which is prone to landslides. In geotechnical analysis, one way to optimize the geometry of the mine slope is to determine the slope-forming parameters including the angle and height of the slope to get the value of the slope safety criteria. In this geotechnical study, the finite element method (FEM) is used to analyze the slope stability of the existing conditions on three slope models based on cross-sectional lines of local topographic maps. From the value of the safety factor obtained from the three models, then an analysis is carried out to determine the single slope and the overall slope which can later be recommended. In addition, to determine the potential for landslides that can occur at the research site, kinematic analysis is used. Slope stability analysis with three models based on cross-sectional lines obtained SRF values A-A' of 1.88, B-B' of 1.68 and for C-C' of 1.86. In making the model for a single slope made with three variations in height which shows the condition of the slope is still stable with the acquisition of SRF values> 1.3. The result of the analysis is a slope with a geometry of 15m high and a slope of 70°, where the overall slope is modeled in tiers with the SRF value obtained is still above 1.3, namely the overall slope height is 75 m with an overall slope of 64.30°. Abstrak. Kajian geoteknik merupakan fungsi penting dalam mengatasi masalah stabilitas lereng yang rentan terjadinya kelongsoran. Dalam analisis geoteknik salah satu cara mengoptimalkan geometri lereng tambang yaitu dengan menentukan parameter pembentuk lereng meliputi sudut serta ketinggian lereng untuk mendapatkan nilai kriteria keamanan lereng. Dalam kajian geoteknik pada penelitian ini menggunakan metode elemen hingga (FEM) untuk menganalisis kestabilan lereng kondisi eksisting pada tiga model lereng berdasarkan garis penampang peta topografi lokal. Dari nilai faktor keamanan yang diperoleh dari tiga model tersebut, kemudian dilakukan analisis untuk menentukan lereng tunggal dan lereng keseluruhan yang nantinya dapat direkomendasikan. Selain itu, untuk mengetahui potensi longsoran yang dapat terjadi pada lokasi penelitian digunakan analisis kinematik. Analisis kestabilan lereng dengan tiga model berdasarkan garis penampang diperoleh nilai SRF A-A’ sebesar 1,88, B-B’ sebesar 1,68 dan untuk C-C’ sebesar 1,86. Pada pembuatan model untuk lereng tunggal dibuat dengan tiga variasi ketinggian yang menunjukkan kondisi lereng masih stabil dengan perolehan nilai SRF >1,3. Hasil dari analisis adalah lereng dengan geometri tinggi 15m dan kemiringan 70°, dimana lereng keseluruhan dimodelkan berjenjang dengan nilai SRF yang diperoleh masih diatas 1,3 yaitu pada ketinggian lereng keseluruhan 75 m dengan kemiringan keseluruhan yaitu 64,30°.